Mengenalkan Guru dan Tenaga Pendidik tentang Pencegahan Kekerasan terhadap Anak di SDN Cibatu 02 Kabupaten Cikarang - Prawitasari, Nining Yurista; Sayudi, Akbar; Juhriati, Ika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Community service activities are expected to provide understanding to the local area. The main focus of this action is educators and teachers at SDN Cibatu 02. Generally, they do not have enough understanding of child protection and law enforcement and have not received consultation or training on child protection laws. Therefore, sufficient knowledge is needed through legal counseling to address partner issues regarding efforts to prevent violence against students as legal protection based on the Child Protection Law. Legal consultation efforts aim to provide legal knowledge about child protection to students and teachers. Then continued by asking and answering questions, using learning activities and essay discussion methods at local schools and offering quizzes, pre-tests, and post-tests. The results of this activity are expected to demonstrate the importance of increasing awareness of child protection in improving teachers' legal knowledge and awareness as educators of their duties, rights, and obligations to the school in protecting their students.